2023
DOI: 10.3390/vaccines11020466
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Vaccine Hesitancy among New Jersey Teachers and Impacts of Vaccination Information Dissemination

Abstract: Vaccine hesitancy continues to be prevalent in the United States, especially in relation to the COVID-19 vaccines and its boosters, which have been made increasingly available for public use as the pandemic has progressed. There continues to be concern surrounding the safety and health of secondary or high school education professionals as they transition back to in-person learning and working opportunities. The present study highlights how information dissemination regarding the COVID-19 vaccine has varied am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…High-quality provider recommendations to vaccinate are strongly associated with adolescent vaccination in general [ 59 , 60 , 61 , 62 ]. Another study in NJ among high school teachers also found that primary care providers, in addition to the CDC and state health department, were trusted COVID-19 vaccination sources [ 63 ]. Our participants also valued unbiased, scientific evidence regarding vaccination so that they could personally weigh the benefits and risks [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…High-quality provider recommendations to vaccinate are strongly associated with adolescent vaccination in general [ 59 , 60 , 61 , 62 ]. Another study in NJ among high school teachers also found that primary care providers, in addition to the CDC and state health department, were trusted COVID-19 vaccination sources [ 63 ]. Our participants also valued unbiased, scientific evidence regarding vaccination so that they could personally weigh the benefits and risks [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Throughout the COVID-19 pandemic, the NJSS published many papers regarding actions and perceptions among teachers' responses to different COVID-19-related issues. These studies focused on vaccine practices [42,43], teacher mental health [44], perceptions of WBL activities during the pandemic [45], trends in COVID-19 outbreaks [46], and apprenticeships in NJ [47]. These studies are consistent with the NJSS mission to continue understanding NJ experiences and needs during the pandemic and to ensure safe schools for teachers and students.…”
Section: Discussionmentioning
confidence: 98%
“…After data management and initial descriptive statistics were computed for the entire State of NJ study sample, for each survey question/variable the data were stratified by the vaccination status, number of doses of vaccine, and booster status at the time of the survey; gender; age; county of work; race/ethnicity; and teaching experience (both overall and in NJ). For justification of the county separation, please reference our previously published study [25]. In this study, those who did not get vaccinated are considered vaccine-hesitant.…”
Section: Discussionmentioning
confidence: 99%
“…The survey used in this study included 28 questions with multiple parts about vaccine status, experience specifically with the COVID-19 vaccine, vaccine perceptions and opinions regarding the ease of obtaining the vaccine, factors that were important to obtaining the vaccine, factors that helped convince the participants the vaccine was safe to get, self-reported COVID-19 case information (including hospitalization status), and demographics. Other factors, such as COVID-19 vaccine education, trusted sources of information, safety practices, and concerns about contracting COVID-19, were explored in a previously published study [25]. For more information on the survey questions, please read our previously published study [25].…”
Section: Survey Detailsmentioning
confidence: 99%
See 1 more Smart Citation